2018
DOI: 10.1371/journal.pone.0195783
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of the lipophorin receptor in the crustacean ectoparasite Lepeophtheirus salmonis

Abstract: The Salmon louse (Lepeophtheirus salmonis) is a marine ectoparasite of salmonid fish in the Northern Hemisphere and considered as a major challenge in aquaculture and a threat to wild populations of salmonids. Adult female lice produce a large number of lipid-rich eggs, however, the mechanism of maternal lipid transport into developing eggs during salmon louse reproduction has not been described. In the present study, a full-length L. salmonis lipophorin receptor (LsLpR) consisting of 16 exons was obtained by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 66 publications
(81 reference statements)
0
5
0
Order By: Relevance
“…4). Lipid metabolism is also down regulated after attachment presumably due to the change of nutrition from stored lipids [127] to ingested host tissues. Furthermore, several copies of a gene with Blast hit to the protein Timeless [128], known for regulating circadian rhythm in Drosophila , are among the down regulated transcripts.…”
Section: Resultsmentioning
confidence: 99%
“…4). Lipid metabolism is also down regulated after attachment presumably due to the change of nutrition from stored lipids [127] to ingested host tissues. Furthermore, several copies of a gene with Blast hit to the protein Timeless [128], known for regulating circadian rhythm in Drosophila , are among the down regulated transcripts.…”
Section: Resultsmentioning
confidence: 99%
“…The expression analysis of different tissues of female louse suggests that LsLp1 and LsLp2 are synthesized by the sub-epidermal tissue and the intestine and involved in the recruitment of lipids to different lice tissues. Lipid staining results suggest a major transport of lipids in adult female lice to the ovaries and developing oocytes in the genital segment [ 53 , 54 ]. Therefore, it is speculated that lipids from intestine are taken up by apolipoproteins produced in intestine or sub-cuticular tissues, and transported to the ovaries and oocytes via the hemolymph.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in L. salmonis have shown that maternal lipids supplied to the maturing eggs during vitellogenesis are essential for growth and development of larvae [ 53 ]. Presence of lipophorin receptor [ 54 ] in ovaries and eggs suggest internalization of lipoproteins mediated through endocytosis, but the transport of lipids to the growing oocytes is undescribed.…”
Section: Introductionmentioning
confidence: 99%
“…Other sequences relevant for cell development and reproduction were up-regulated in T. stylifera collected on May 23rd, such as me31b (ATP-Dependent RNA Helicase), Vldlr (Very Low-Density Lipoprotein Receptor) and Vasa (ATP-Dependent RNA Helicase Vasa). These genes are known to play key roles in germ cell formation [100,101] as well as in oocyte development and differentiation [102][103][104].…”
Section: Discussionmentioning
confidence: 99%